A method for preparing a zeolite-supported composite material for lithium ion extraction
Through the use of ziggle load composite materials during lithium ion extraction, combined with medium -pels high -silicon Y -shaped blood and non -fixed Al (OH) 3 powder, the problem of high cost of high and low sustainability of the existing lithium ion adsorbent. Achieve efficient, low -cost lithium ion adsorption effects.
Patent Information
- Application Number
- CN202310125102.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-02-16
AI Technical Summary
The existing lithium-ion adsorbents have high cost and high consumption, high dissolution rate of lithium-ion sieve skeletons, and low sustainable use rate.
The blood -load composite material is used, and the high -silicon Y -shaped boiler is synthetic as a carrier, combined with non -fixed Al (OH) 3 powder and LICL · H2O, forming aluminum lithium ion adsorption agents to improve adsorption selectivity and stability.
A low -cost, efficient lithium ion adsorption is achieved, the dissolving loss rate of lithium ion sieve skeleton has been reduced, the sustainable utilization rate of composite materials is improved, and the process process is simplified.
Smart Images

Figure CN116272851B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the preparation of a composite material, and in particular to a method for preparing a zeolite-loaded composite material for lithium ion extraction, belonging to the field of salt lake brine extraction. Background Art
[0002] The main lithium extraction technologies for salt lake brines include precipitation, extraction, ion exchange adsorption, calcination leaching, electrodialysis, evaporation crystallization, and salting-out. Among these technologies, adsorption is not only suitable for salt lake brines with high magnesium-to-lithium ratios, but is also simple to operate, environmentally friendly, and low-cost, making it recognized as the best method for extracting lithium from salt lake brines.
[0003] Lithium extraction by adsorption involves using an adsorbent that selectively adsorbs lithium ions to adsorb lithium ions. The lithium ions are then eluted and concentrated with an eluent to separate them from other impurity ions. The core of lithium extraction by adsorption is the development of an adsorbent with excellent performance. This requires the adsorbent to have strong selectivity for lithium ions, stable adsorption and desorption properties, simple preparation methods, and economical pricing. Lithium ion adsorbents used in the adsorption method are primarily divided into organic and inorganic adsorbents. Inorganic adsorbents primarily include aluminum-based adsorbents, layered ion exchange adsorbents, and titanium-, antimony-, and manganese-based lithium ion sieves.
[0004] Aluminum-based adsorbents primarily include amorphous aluminum hydroxide and aluminum salt adsorbents. These are easy to prepare, highly selective, and stable, making them promising lithium-ion adsorbents. However, currently developed materials are generally powdered, with poor permeability and fluidity, and exhibit high dissolution loss during exchange, resulting in high economic costs and energy consumption, making recycling difficult. Layered ion exchange adsorbents primarily include arsenates and phosphates of high-valent metals. However, these adsorbents contain the toxic element arsenic, which can pollute salt lakes and the surrounding environment during lithium extraction, making environmental recovery difficult. Layered manganese dioxide adsorbents can also be used to adsorb lithium ions from salt lake brine and exhibit high adsorption selectivity. However, their preparation is complex, difficult to control, and have a low specific surface area. Titanium-based lithium ion adsorbents are metatitanate-type lithium ion adsorbents prepared using titanium dioxide as the titanium source and lithium hydroxide or lithium carbonate as the lithium source. They have high selectivity for lithium ions, a high saturated adsorption capacity, a high elution rate, and a low dissolution rate. However, like most powder adsorption materials, these adsorbents are difficult to operate, have a slow adsorption rate, and a long adsorption saturation time. Antimony-based lithium ion sieves, based on the adsorption principle of ion exchange between hydrogen ions and lithium ions, have high selectivity for lithium ions, a large adsorption capacity, and low dissolution loss. They are a promising lithium adsorbent. However, research on this type of adsorbent started relatively late, and many technical approaches are not mature enough. Further research on structural doping and surface modification is needed. Manganese-based lithium ion sieves are produced by reacting lithium and manganese carbonates or oxides in different proportions to form a precursor, which is then acid-eluted. Manganese oxides with a spinel structure have the advantages of large adsorption capacity, low cost, and simple operation. They are currently the most studied and most promising new, efficient, and green adsorbents. However, their unstable structure during the acid elution process limits their industrial development. Summary of the Invention
[0005] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing a zeolite-loaded composite material for lithium ion extraction, which solves the problems of high adsorbent cost and large consumption, high dissolution rate of lithium ion sieve framework and low sustainable utilization rate in the prior art, and realizes the preparation of a composite material with low cost, no pollution, high lithium ion adsorption selectivity and strong stability and high sustainable utilization rate.
[0006] The technical solutions adopted in the present invention are as follows:
[0007] A method for preparing a zeolite-supported composite material for lithium ion extraction comprises the following steps:
[0008] Step 1) synthesizing a medium-pore high-silicon Y-type zeolite;
[0009] Step 2) Synthesis of amorphous Al(OH)3 powder;
[0010] Step 3) dissolving the amorphous Al(OH)3 powder from step 2) in ultrapure water and stirring until completely dispersed; then adding the medium-pore high-silica Y-type zeolite synthesized in step 1), adding LiCl·H2O and reacting at 50-75°C for 20-40 hours, filtering, fully washing, drying, and calcining at 400-500°C for 12-48 hours to obtain a zeolite-loaded composite material for lithium ion extraction, wherein the mass ratio of the amorphous Al(OH)3 powder to the ultrapure water is (0.8-1.1):(98-100), and the mass ratio of the amorphous Al(OH)3 powder to the LiCl·H2O is (0.9-1.2):(1.02-1.28).
[0011] Furthermore, the step 1) synthesizing the mesoporous high-silica Y-type zeolite by using an organic amine-free hydrothermal system comprises the following steps:
[0012] Sodium metaaluminate, fumed silica, water and anhydrous ethanol are used as raw materials and prepared in a molar ratio of (8-12):12:160:(5-17.15);
[0013] Sodium metaaluminate is added to water according to the formula amount and stirred for 0.5-1 hour. Then, sodium hydroxide is added to adjust the pH to 7-8. Then, anhydrous ethanol is added according to the formula amount, and ultrasonic treatment is performed for 2-10 minutes. Finally, fumed silica is added according to the formula amount. After aging in a water bath at 22-27°C for 12-36 hours, the resulting gel mixture is crystallized in an oven at 60-90°C for 6-48 hours. After crystallization, the product is washed with distilled water until neutral, boiled in a sodium chloride solution with a mass percentage concentration of 28-32%, and dried to obtain a medium-porous high-silica Y-type zeolite.
[0014] Furthermore, the step 1) synthesizing the mesoporous high-silica Y-type zeolite by the CTAB / AESA method comprises the following steps:
[0015] Sodium metaaluminate, fumed silica, water and CTAB / AESA are used as raw materials and prepared in a molar ratio of (8-9):12:160:(11-13);
[0016] Sodium metaaluminate is added to water according to the formula amount and stirred for 0.5-1 hour. Then, sodium hydroxide is added to adjust the pH to 7-8. Then, the formula amount of CTAB / AESA is added and stirred thoroughly. Then, the formula amount of fumed silica is added. After aging in a water bath at 22-27°C for 12-36 hours, the resulting gel mixture is crystallized in an oven at 60-90°C for 6-48 hours. After the crystallization is completed, the product is washed with distilled water until neutral, placed in a sodium chloride solution with a mass percentage concentration of 28-32%, boiled for 2-4 hours, and dried to obtain a medium-porous high-silica Y-type zeolite.
[0017] Furthermore, the step 1) synthesizing the mesoporous high-silica Y-type zeolite by the TPOAC method comprises the following steps:
[0018] (1) A structure directing agent is prepared by using sodium metaaluminate, fumed silica and water as raw materials in a molar ratio of (30-35): (12-16): (322-326);
[0019] Add sodium metaaluminate to water according to the formula amount, stir for 25-35 minutes, then add sodium hydroxide to adjust the pH to 7-8, then add the formula amount of fumed silica, stir for 2-24 hours and use as a structure directing agent for later use;
[0020] (2) preparing a medium-pore high-silica Y-type zeolite using sodium metaaluminate, fumed silica, water, hydrochloric acid, TPOAC, and a structure-directing agent as raw materials in a molar ratio of (4.2-4.8):(8.2-8.6):210:(4-5):0.09:11.7;
[0021] At room temperature, hydrochloric acid and sodium metaaluminate are dissolved in water according to the formula amount, stirred for 0.5-1 hour to obtain a white solution, fumed silica is added according to the formula amount, and after stirring for 2-5 hours, the structure directing agent prepared in step (1) is added dropwise according to the formula amount, and after stirring for another 0.5-1 hour, TPOAC is added dropwise in the formula amount, and then crystallized in an oven at 60-90° C. for 72-120 hours; after the crystallization is completed, the product is washed with distilled water until neutral, and placed in a sodium chloride solution with a mass percentage concentration of 28-32 and boiled for 2-4 hours. After drying, it is calcined in a muffle furnace at 500-600° C. to obtain a medium-pore high-silica Y-type zeolite.
[0022] Furthermore, the hydrochloric acid is dilute hydrochloric acid with a mass percent concentration of 6.5-7.0 wt%.
[0023] Furthermore, the pore size of the medium-pore high-silicon Y-type zeolite is 2-30 nm, and the Si / Al ratio is 3-20.
[0024] Further, the step 2) synthesis of amorphous Al(OH)3:
[0025] Prepare 500 ml of sodium aluminate solution, add 2-4 ml of polyethylene glycol 1000 solution to the solution, add hydrochloric acid solution dropwise to the solution with stirring until the pH is 5.8-6.2, reaching the reaction end point, continue the reaction for 15-25 minutes, filter and separate the product, wash and dry it to obtain amorphous Al(OH)3 powder.
[0026] Furthermore, the molar concentration of the sodium metaaluminate solution is 0.4-0.6 mol / L.
[0027] Furthermore, the mass percentage concentration of the polyethylene glycol 1000 solution is 8-12%.
[0028] Furthermore, the molar concentration of the hydrochloric acid solution in the synthesis of amorphous Al(OH)3 in step 2) is 1.8-2.1 mol / L.
[0029] The beneficial effects of the present invention are as follows: the composite material provided by the present invention loads an aluminum-based lithium ion adsorbent on a synthetic zeolite material, and has good selective adsorption for lithium ions; the aluminum-based lithium ion adsorbent is tightly connected in the synthetic zeolite carrier, and the dissolution rate of the ion sieve skeleton is low, and the overall sustainable utilization rate of the composite material is high; the synthetic zeolite is a porous adsorption material, and compared with natural zeolite as an adsorbent carrier, it has a larger specific surface area and no impurities are produced, which can simplify subsequent process flow; as the silicon-aluminum ratio of the synthetic zeolite material increases, the stability of the composite material is further enhanced, and it is suitable for application in large-scale lithium extraction processes; the synthesis and preparation cost of the composite material is low, the process is simple, and it is easy to industrialize.
[0030] The specific advantages are as follows:
[0031] 1. The use of artificially synthesized high-silicon Y-type zeolite as a lithium ion adsorbent carrier has a larger specific surface area than natural zeolite as an adsorbent carrier. Therefore, it effectively solves the problem of low lithium ion adsorption rate in high magnesium-lithium ratio salt lake brine, thereby achieving good adsorption selectivity for lithium ions;
[0032] 2. The use of aluminum-based lithium ion adsorbents effectively solves the problems of high cost and complex process of the original adsorbents, thereby achieving the preparation of lithium ion adsorbents with low cost, simple process and good application prospects;
[0033] 3. Since the aluminum-based lithium ion adsorbent is tightly linked in the artificially synthesized high-silicon Y-type zeolite carrier, it effectively solves the problems of high dissolution rate and low reuse rate of the original ion sieve framework, thereby enhancing the stability of the composite material and improving its overall sustainable utilization rate.
[0034] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0036] Figure 1 Schematic diagram of the structure of Y-type zeolite;
[0037] Figure 2 Schematic diagram of the crystal structure of diamond;
[0038] Figure 3 For β cage. DETAILED DESCRIPTION
[0039] The following describes the embodiments of the present invention through specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0040] Exemplary embodiments of the present invention will now be described with reference to the accompanying drawings. However, the present invention may be embodied in many different forms and is not limited to the embodiments described herein. These embodiments are provided so as to provide a thorough and complete disclosure of the present invention and fully convey the scope of the present invention to those skilled in the art. The terms used in the exemplary embodiments shown in the accompanying drawings are not intended to limit the present invention.
[0041] Unless otherwise specified, the terms used herein (including technical terms) have the meanings commonly understood by those skilled in the art. In addition, it is understood that terms defined in commonly used dictionaries should be understood to have the same meanings as those in the context of the relevant fields, and should not be understood as idealized or overly formal meanings.
[0042] Description of relevant terms involved in this invention:
[0043] Topology: Topology is the process of abstracting entities into "points" whose size and shape are independent, and the paths connecting entities into "lines." The relationship between these points and lines is then represented graphically. The purpose of this process is to study the connections between these points and lines. A graph representing the relationships between points and lines is called a topological graph. Topology and geometry are two different mathematical concepts. In geometry, the positional relationships between points and lines are examined, or in other words, geometry emphasizes the shape and size formed by these points and lines. For example, a trapezoid, square, parallelogram, and circle are all different geometric structures. However, from a topological perspective, because the connections between points and lines are the same, they share the same topological structure: a ring. In other words, different geometric structures can share the same topological structure.
[0044] Silicon-aluminum ratio (SAR): The silicon-aluminum ratio refers to the ratio of the silicon content to the aluminum content in a material. There are generally two types of ratios: mass ratio, which is the ratio of the total mass of one element to the mass of one or more other elements, calculated as m1:m2; and molar ratio, which is the ratio of the amount of one element to the amount of one or more other elements, calculated as n1:n2.
[0045] Specific surface area: Specific surface area refers to the surface area per unit mass of a porous solid. Because the external surface area of a solid is negligible relative to its internal surface area, specific surface area usually refers to the internal surface area. The most common unit is square meters per gram.
[0046] CTAB: Cetyltrimethylammonium Bromide.
[0047] AESA:Ammonium Alcohol Ether Sulphate, fatty alcohol polyoxyethylene ether ammonium sulfate.
[0048] TPOAC:Dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride.
[0049] Ultrapure water, also known as UP water, is water with a resistivity of 18MΩ*cm (25°C).
[0050] PEG1000: average molecular weight is 1000.
[0051] ICP: Inductively Coupled Plasma Spectrometer.
[0052] The present invention provides a method for preparing a zeolite-supported composite material for lithium ion extraction, comprising the following steps: Step 1) synthesizing a mesoporous high-silicon Y-type zeolite;
[0053] Step 2) Synthesis of amorphous Al(OH)3 powder;
[0054] Step 3) dissolving the amorphous Al(OH)3 powder from step 2) in ultrapure water and stirring until completely dispersed; then adding the medium-pore high-silica Y-type zeolite synthesized in step 1), adding LiCl·H2O and reacting at 50-75°C for 20-40 hours, filtering, fully washing, drying, and calcining at 400-500°C for 12-48 hours to obtain a zeolite-loaded composite material for lithium ion extraction, wherein the mass ratio of the amorphous Al(OH)3 powder to the ultrapure water is (0.8-1.1):(98-100), and the mass ratio of the amorphous Al(OH)3 powder to the LiCl·H2O is (0.9-1.2):(1.02-1.28).
[0055] Preferably, the mass ratio of the amorphous Al(OH)3 powder to ultrapure water is 1:100, and the mass ratio of the amorphous Al(OH)3 powder to LiCl·H2O is 1:1.21.
[0056] The invention forms an aluminum-based lithium ion adsorbent by using amorphous Al(OH)3 powder and mesoporous high-silicon Y-type zeolite as a carrier and adding LiCl·H2O.
[0057] Furthermore, the present invention provides the following three methods for synthesizing medium-pore high-silica Y-type zeolite:
[0058] The first method: the step 1) synthesizing the mesoporous high-silica Y-type zeolite adopts an organic amine-free hydrothermal system to synthesize the mesoporous high-silica Y-type zeolite, comprising the following steps:
[0059] Sodium metaaluminate, fumed silica, water and anhydrous ethanol are used as raw materials and prepared in a molar ratio of (8-12):12:160:(5-17.15);
[0060] Sodium metaaluminate is added to water according to the formula amount and stirred for 0.5-1 hour. Then, sodium hydroxide is added to adjust the pH to 7-8. Then, anhydrous ethanol is added according to the formula amount, and ultrasonic treatment is performed for 2-10 minutes. Finally, fumed silica is added according to the formula amount. After aging in a water bath at 22-27°C for 12-36 hours, the resulting gel mixture is crystallized in an oven at 60-90°C for 6-48 hours. After crystallization, the product is washed with distilled water until neutral, boiled in a sodium chloride solution with a mass percentage concentration of 28-32%, and dried to obtain a medium-porous high-silica Y-type zeolite.
[0061] The second method: the step 1) synthesizing the mesoporous high-silica Y-type zeolite adopts the CTAB / AESA method to synthesize the mesoporous high-silica Y-type zeolite, comprising the following steps:
[0062] Sodium metaaluminate, fumed silica, water and CTAB / AESA are used as raw materials and prepared in a molar ratio of (8-9):12:160:(11-13);
[0063] Sodium metaaluminate is added to water according to the formula amount and stirred for 0.5-1 hour. Then, sodium hydroxide is added to adjust the pH to 7-8. Then, the formula amount of CTAB / AESA is added and stirred thoroughly. Then, the formula amount of fumed silica is added. After aging in a water bath at 22-27°C for 12-36 hours, the resulting gel mixture is crystallized in an oven at 60-90°C for 6-48 hours. After the crystallization is completed, the product is washed with distilled water until neutral, placed in a sodium chloride solution with a mass percentage concentration of 28-32%, boiled for 2-4 hours, and dried to obtain a medium-porous high-silica Y-type zeolite.
[0064] Preferably, the sodium aluminate, fumed silica, water and CTAB / AESA are prepared in a molar ratio of 8-9:12:160:12.
[0065] The third method: the step 1) synthesizing the mesoporous high-silica Y-type zeolite adopts the TPOAC method to synthesize the mesoporous high-silica Y-type zeolite, comprising the following steps:
[0066] (1) A structure directing agent is prepared by using sodium metaaluminate, fumed silica and water as raw materials in a molar ratio of (30-35): (12-16): (322-326);
[0067] Add sodium metaaluminate to water according to the formula amount, stir for 25-35 minutes, then add sodium hydroxide to adjust the pH to 7-8, then add the formula amount of fumed silica, stir for 2-24 hours and use as a structure directing agent for later use;
[0068] (2) preparing a medium-pore high-silica Y-type zeolite using sodium metaaluminate, fumed silica, water, hydrochloric acid, TPOAC, and a structure-directing agent as raw materials in a molar ratio of (4.2-4.8):(8.2-8.6):210:(4-5):0.09:11.7;
[0069] At room temperature, hydrochloric acid and sodium metaaluminate are dissolved in water according to the formula amount, stirred for 0.5-1 hour to obtain a white solution, fumed silica is added according to the formula amount, and after stirring for 2-5 hours, the structure directing agent prepared in step (1) is added dropwise according to the formula amount, and after stirring for another 0.5-1 hour, TPOAC is added dropwise in the formula amount, and then crystallized in an oven at 60-90° C. for 72-120 hours; after the crystallization is completed, the product is washed with distilled water until neutral, and placed in a sodium chloride solution with a mass percentage concentration of 28-32 and boiled for 2-4 hours. After drying, it is calcined in a muffle furnace at 500-600° C. to obtain a medium-pore high-silica Y-type zeolite.
[0070] Preferably, the sodium aluminate, fumed silica and water are prepared into a structure directing agent in a molar ratio of 32:15:325; preferably, the sodium aluminate, fumed silica, water, hydrochloric acid, TPOAC and structure directing agent are prepared into a medium-pore high-silicon Y-type zeolite in a molar ratio of 4.6:8.4:210:4-5:0.09:11.7.
[0071] Furthermore, the hydrochloric acid is dilute hydrochloric acid with a mass percentage concentration of 6.5-7.0 wt %. Preferably, the hydrochloric acid is dilute hydrochloric acid with a mass percentage concentration of 6.8 wt %.
[0072] Preferably, in the above three embodiments, the mass percentage concentration of the sodium chloride solution is 30%.
[0073] The three types of medium-pore high-silicon Y-type zeolites of the present invention were tested by XPS and specific surface area and pore size analyzers. The Si / Al ratio was between 3-30, and the pore size distribution was between 2-50nm. XPS: X-ray photoelectron spectrometer, XPS can measure the elemental composition, empirical formula, element chemical valence and electronic state in the material. A beam of X-rays is used to excite the solid surface, and the kinetic energy of the electrons emitted within 1-10nm of the surface of the analyzed material is measured at the same time. By counting the excited electrons that exceed a certain kinetic energy, a photoelectron spectrum can be obtained. The peaks that appear in the photoelectron spectrum are electrons of a certain characteristic energy emitted from atoms. The energy and intensity of the photoelectron peaks can be used for qualitative and quantitative analysis of all surface elements except H and He.
[0074] Due to the structure of Y-type zeolite (such as Figure 1 ) and the two structures of diamond (such as Figure 2 ) is very similar, and its topological structure shows that: when using β cage (such as Figure 3) replaces the carbon atoms in the diamond structure, and then connects the adjacent β cages through six-membered rings in the form of TOT bonds (T is the central atom, which is Si or Al), forming the basic structure of the Y-type zeolite crystal. Y-type zeolite is an artificially synthesized eight-sided zeolite with a topological structure, a larger pore size among zeolites, and a larger specific surface area. Compared with natural zeolites, it has the advantages of high purity, no impurities, adjustable silicon-aluminum ratio, and large specific surface area. Therefore, the composite material of the present invention selects artificially synthesized zeolite as a lithium ion adsorbent carrier. However, the structural stability and hydrothermal stability of Y-type zeolite with a low silicon-aluminum ratio are relatively poor. The present invention increases the structural stability and hydrothermal stability by increasing the silicon-aluminum ratio (SAR) of the skeleton, which is beneficial for the adsorbent to maintain its performance during long-term use. At the same time, the higher the aluminum content in the zeolite skeleton, the stronger its ion exchange capacity. The medium-pore high-silicon Y-type zeolite of the present invention has the characteristics of small grain size, large external specific surface area, shortened pores, and increased exposed pores, which can effectively improve the adsorption capacity and adsorption efficiency.
[0075] Further, the step 2) synthesis of amorphous Al(OH)3:
[0076] Prepare 500 ml of sodium aluminate solution, add 2-4 ml of polyethylene glycol 1000 solution to the solution, add hydrochloric acid solution dropwise to the solution with stirring until the pH is 5.8-6.2, reaching the reaction end point, continue the reaction for 15-25 minutes, filter and separate the product, wash and dry it to obtain amorphous Al(OH)3 powder.
[0077] Furthermore, the molar concentration of the sodium metaaluminate solution is 0.4-0.6 mol / L.
[0078] Furthermore, the mass percentage concentration of the polyethylene glycol 1000 solution is 8-12%.
[0079] Furthermore, the molar concentration of the hydrochloric acid solution is 1.8-2.1 mol / L.
[0080] Preferably, 500 ml of a 0.5 mol / L sodium aluminate solution is prepared, 3 ml of a 10% by mass polyethylene glycol 1000 solution is added to the solution, and 2 mol / L hydrochloric acid solution is added dropwise to the solution while stirring until the pH is 6 to reach the reaction endpoint, the reaction is continued for 20 minutes, the product is separated by suction, washed and dried to obtain amorphous Al(OH)3 powder.
[0081] The medium-pore high-silicon Y-type zeolite prepared by the method has a pore diameter of 2-30 nm and a Si / Al ratio of 3-20.
[0082] Based on the above preparation method, the present invention provides the following specific embodiments:
[0083] Example 1:
[0084] The present invention provides a method for preparing a zeolite-supported composite material for lithium ion extraction, comprising the following steps:
[0085] Step 1) Synthesis of medium-pore high-silicon Y-type zeolite
[0086] The synthesis of mesoporous high-silica Y-type zeolite by an organic amine-free hydrothermal system comprises the following steps:
[0087] Sodium metaaluminate, fumed silica, water and anhydrous ethanol are used as raw materials and prepared in a molar ratio of 10:12:160:10;
[0088] Sodium metaaluminate is added to water according to the formula amount and stirred for 0.5-1 hour. Then, sodium hydroxide is added to adjust the pH to 7.5. Then, anhydrous ethanol is added according to the formula amount, and ultrasonic treatment is performed for 5 minutes. Finally, a formula amount of fumed silica is added, and after aging in a 25°C water bath for 24 hours, the resulting gel mixture is crystallized in an 80°C oven for 24 hours. After the crystallization is completed, the product is washed with distilled water until neutral, placed in a 30% by mass sodium chloride solution, boiled for 3 hours, and dried to obtain a medium-porous high-silica Y-type zeolite.
[0089] Step 2) Synthesis of amorphous Al(OH)3 powder
[0090] Prepare 500 ml of 0.5 mol / L sodium aluminate solution, add 3 ml of 10% by mass polyethylene glycol 1000 solution to the solution, add 2 mol / L hydrochloric acid solution dropwise to the solution while stirring until the pH reaches 6, reaching the reaction endpoint, continue the reaction for 20 minutes, filter and separate the product, wash and dry it to obtain amorphous Al(OH)3 powder.
[0091] Step 3) dissolving the amorphous Al(OH)3 powder of step 2) in ultrapure water and stirring until completely dispersed; then adding the medium-porous high-silica Y-type zeolite synthesized in step 1), adding LiCl·H2O and reacting at 60°C for 30 hours, filtering, fully washing, drying, and calcining at 450°C for 24 hours to obtain a zeolite-loaded composite material for lithium ion extraction, wherein the mass ratio of amorphous Al(OH)3 powder to ultrapure water is 1:100, and the mass ratio of amorphous Al(OH)3 powder to LiCl·H2O is 1:1.21.
[0092] After testing: zeolite accounts for 92.5% of the mass, the silicon-aluminum ratio is about 3.50, the grain size is about 320nm, and the aluminum-based lithium ion sieve accounts for 4.1% of the mass; among them, the silicon-aluminum ratio is detected by XPS, and the grain size is detected by SEM; SEM is a scanning electron microscope.
[0093] The specific surface area of the zeolite-supported composite material for lithium ion extraction is 60.4 m2 / g, pore size is about 9-11nm.
[0094] Example 2:
[0095] The difference from Example 1 is that the step 1) synthesizing the mesoporous high-silica Y-type zeolite adopts the CTAB / AESA method to synthesize the mesoporous high-silica Y-type zeolite, comprising the following steps:
[0096] Sodium metaaluminate, fumed silica, water and CTAB / AESA are used as raw materials in a molar ratio of 8:12:160:12.
[0097] Sodium metaaluminate is added to water according to the formula amount and stirred for 0.5-1 hour. Then, sodium hydroxide is added to adjust the pH to 7. Then, the formula amount of CTAB / AESA is added and stirred thoroughly. Then, the formula amount of fumed silica is added. After aging in a 25°C water bath for 24 hours, the resulting gel mixture is crystallized in an 80°C oven for 24 hours. After the crystallization is completed, the product is washed with distilled water until neutral, placed in a 30% by mass sodium chloride solution, boiled for 3 hours, and dried to obtain a medium-porous high-silica Y-type zeolite.
[0098] After testing: zeolite accounts for 93.1% of the mass, the silicon-aluminum ratio is about 3.19, the grain size is about 400nm, and the aluminum-based lithium ion sieve accounts for 4.7% of the mass; among them, the silicon-aluminum ratio is detected by XPS, and the grain size is detected by SEM; SEM is a scanning electron microscope.
[0099] The specific surface area of the zeolite-supported composite material for lithium ion extraction is 61.4 m 2 / g, pore size is about 13-15nm.
[0100] Example 3:
[0101] The difference from Example 1 is that the step 1) synthesizing the mesoporous high-silica Y-type zeolite adopts the TPOAC method to synthesize the mesoporous high-silica Y-type zeolite, comprising the following steps:
[0102] (1) A structure directing agent was prepared using sodium metaaluminate, fumed silica, and water as raw materials in a molar ratio of 32:15:325;
[0103] Add sodium metaaluminate according to the formula amount to water, stir for 30 minutes, add sodium hydroxide to adjust the pH to 8, then add the formula amount of fumed silica, stir for 12 hours and use as a structure directing agent;
[0104] (2) preparing a medium-pore high-silica Y-type zeolite using sodium metaaluminate, fumed silica, water, hydrochloric acid, TPOAC, and a structure-directing agent as raw materials in a molar ratio of 4.6:8.4:210:4.5:0.09:11.7;
[0105] The hydrochloric acid is dilute hydrochloric acid, and its mass percent concentration is 6.8 wt%.
[0106] At room temperature, hydrochloric acid and sodium metaaluminate are dissolved in water according to the formula amount, stirred for 0.5-1h to obtain a white solution, fumed silica is added according to the formula amount, and after stirring for 4h, the structure directing agent prepared in step (1) is added dropwise according to the formula amount, and after stirring for 1h again, TPOAC is added dropwise in the formula amount, and then crystallized in an oven at 75°C for 100h; after the crystallization is completed, the product is washed with distilled water until neutral, and placed in a sodium chloride solution with a mass percentage concentration of 30 and boiled for 2-4h. After drying, it is calcined in a muffle furnace at 500-600°C to obtain a medium-pore high-silica Y-type zeolite.
[0107] After testing: zeolite accounts for 94.1% of the mass, the silicon-aluminum ratio is about 3.23, the grain size is about 380nm, and the aluminum-based lithium ion sieve accounts for 4.8% of the mass; among them, the silicon-aluminum ratio is detected by XPS, and the grain size is detected by SEM; SEM is a scanning electron microscope.
[0108] The specific surface area of the zeolite-supported composite material for lithium ion extraction is 51.5 m 2 / g, pore size is about 15-17nm.
[0109] Example 4:
[0110] The present invention provides a method for preparing a zeolite-supported composite material for lithium ion extraction, comprising the following steps:
[0111] The reactants are mixed in molar ratio: 8NaAlO2:12SiO2:160H2O:10C2H5OH
[0112] (1) Add 4.100 g of sodium aluminate to 18 ml of water;
[0113] (2) Stir the solution at room temperature (20°C) at a speed of about 500 r / min using a magnetic stirrer for 30 min until it is completely dissolved and becomes a transparent solution;
[0114] (3) After waiting for 20 minutes for the solution to become transparent, add sodium hydroxide to adjust the pH to 7.5 and stir for 15 minutes;
[0115] (4) After adding 2.875 g of anhydrous ethanol, ultrasonic treatment was performed in an ultrasonic cleaner for 3 min to ensure that the reactants were completely dissolved;
[0116] (5) Finally, 4.5 g of fumed silica was added, and the mixture was sealed with a plastic film and then placed in a water bath at 25°C for constant temperature aging for 24 h.
[0117] (6) Afterwards, the uniformly stirred gel mixture was poured into a reactor and crystallized in an oven at 60 °C for 20 h;
[0118] (7) After the crystallization is completed, the reactor is placed in a cold water pool for rapid cooling;
[0119] (8) After washing the product with distilled water until neutral, the obtained Y-type zeolite sample was placed in a 30% by mass NaCl solution and boiled for 3 hours;
[0120] (9) Drying at 90°C to obtain medium-pore high-silica Y-type zeolite;
[0121] (10) Prepare 500 ml of 0.5 mol / L NaAlO2 solution;
[0122] (11) Add 3 ml of 10% by mass concentration of polyethylene glycol 1000 (PEG1000) solution to the solution;
[0123] (12) Add 2 mol / L HCl solution dropwise to the solution while stirring until the pH reaches 6, reaching the reaction endpoint, and continue the reaction for 20 minutes;
[0124] (13) separating the product by filtration, washing, and drying to obtain amorphous Al(OH)3 powder;
[0125] (14) Dissolve 5 g of amorphous Al(OH)3 in 500 ml of ultrapure water and stir until completely dispersed;
[0126] (15) adding the prepared medium-pore high-silica Y-type zeolite carrier thereto;
[0127] (16) After heating to 50°C, 6.05 g of LiCl·H2O was added and stirred for 24 h;
[0128] (17) After filtration, the product was thoroughly washed, dried, and calcined in a muffle furnace at 400 °C for 24 h to obtain a zeolite-supported composite material for lithium ion extraction.
[0129] After testing: zeolite accounts for 93.7% of the mass, the silicon-aluminum ratio is about 3.29, the grain size is about 300nm, and the aluminum-based lithium ion sieve accounts for 4.2% of the mass; among them, the silicon-aluminum ratio is detected by XPS, and the grain size is detected by SEM; SEM is a scanning electron microscope.
[0130] The specific surface area of the zeolite-supported composite material for lithium ion extraction is 61.7 m 2 / g, pore size is about 8-10nm.
[0131] Example 5:
[0132] The reactants are mixed in molar ratio: 8NaAlO2:12SiO2:160H2O:12CTAB / AESA
[0133] (1) Add 4.100 g of sodium metaaluminate to 18 ml of distilled water;
[0134] (2) Stir the solution at room temperature (23°C) at a speed of about 500 rpm for 40 min using a magnetic stirrer until it is completely dissolved and becomes a transparent solution;
[0135] (3) After stirring evenly and becoming transparent, add sodium hydroxide to adjust the pH to 7.8;
[0136] (4) After stirring for 20 minutes, 27.311 g of cetyltrimethylammonium bromide (CTAB) or 23.625 g of fatty alcohol polyoxyethylene ether ammonium sulfate (AESE) was added and stirred thoroughly;
[0137] (5) Then, 4.5 g of fumed silica was added, the mixture was sealed with a plastic film, and the mixture was placed in a water bath at 25°C for constant temperature aging for 24 h;
[0138] (6) Afterwards, the uniformly stirred gel mixture was poured into a reactor and crystallized in an oven at 90 °C for 18 h;
[0139] (7) After the crystallization is completed, the reactor is placed in a cold water pool for rapid cooling;
[0140] (8) After washing the product with distilled water until neutral, the obtained Y-type zeolite sample was placed in a 30% by mass NaCl solution and boiled for 3 h;
[0141] (9) Synthetic medium-pore high-silica Y-type zeolite was obtained by drying at 90°C;
[0142] (10) Prepare 500 ml of 0.5 mol / L NaAlO2 solution;
[0143] (11) Add 3 ml of 10% polyethylene glycol 1000 (PEG1000) solution to the solution;
[0144] (12) Add 2 mol / L HCl solution dropwise to the solution while stirring until the pH reaches 6, reaching the reaction endpoint, and continue the reaction for 20 minutes;
[0145] (13) separating the product by filtration, washing, and drying to obtain amorphous Al(OH)3 powder;
[0146] (14) Dissolve 5 g of amorphous Al(OH)3 in 500 ml of ultrapure water and stir until completely dispersed;
[0147] (15) adding the prepared medium-pore high-silica Y-type zeolite carrier thereto;
[0148] (16) After heating to 60°C, 6.05 g of LiCl·H2O was added and stirred for 24 h;
[0149] (17) After filtration, the product was thoroughly washed, dried, and calcined in a muffle furnace at 450 °C for 24 h to obtain a zeolite-supported composite material for lithium ion extraction.
[0150] Using the same instrument as in Example 1, it was determined that the zeolite mass accounted for 94.5%, the silicon-aluminum ratio was approximately 3.22, the grain size was approximately 400 nm, and the aluminum-based lithium ion sieve mass accounted for 3.6%;
[0151] The specific surface area of the zeolite-supported composite material for lithium ion extraction is 58.5 m 2 / g, and the pore size is about 10-15nm.
[0152] Example 6:
[0153] Structure directing agent according to the molar ratio: 32NaAlO2:15SiO2:325H2O
[0154] (1) Add 8.074 g of sodium metaaluminate to 18 ml of distilled water;
[0155] (2) After stirring for 30 minutes until the mixture is uniform and transparent, add sodium hydroxide to adjust the pH to 7.2;
[0156] (3) After dissolution and clarification, add 2.769 g of fumed silica and stir for 20 h as a structure directing agent (SDA).
[0157] (4) Preparation of zeolite molar ratio:
[0158] 4.6NaAlO2:8.4SiO2:210H2O:4.62HCl:0.09TPOAC:11.7SDA
[0159] At room temperature (25°C), dissolve 11 ml of 2 mol / L HCl and 1.796 g of sodium metaaluminate in 18 ml of distilled water and stir for 1 h until a homogeneous milky white solution is obtained.
[0160] Then, 2.4 g of fumed silica was added, and after stirring for 4 h, 1 ml of the structure-directing agent synthesized above was added dropwise;
[0161] After stirring for another 1 h, 0.532 g of 40 wt% dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (TPOAC) was added dropwise;
[0162] After stirring for 1 h, the mixture was charged into a reactor and crystallized at 75 °C for 120 h;
[0163] After the crystallization is completed, the zeolite sample is washed with distilled water until neutral, and then placed in a 30% by mass concentration NaCl solution and boiled for 3 hours;
[0164] After drying at 90℃ and calcining in a muffle furnace at 550℃, the synthesized mesoporous high-silica Y-type zeolite was obtained;
[0165] (5) Prepare 500 ml of 0.5 mol / L NaAlO2 solution;
[0166] (6) Add 3 ml of 10% polyethylene glycol 1000 (PEG1000) solution to the solution;
[0167] (7) Add 2 mol / L HCl solution dropwise to the solution under stirring until the pH reaches 6, reaching the reaction endpoint, and continue the reaction for 20 minutes;
[0168] (8) separating the product by filtration, washing, and drying to obtain amorphous Al(OH)3 powder;
[0169] (9) Dissolve 5 g of amorphous Al(OH)3 in 500 ml of ultrapure water and stir until completely dispersed;
[0170] (10) adding the prepared medium-pore high-silica Y-type zeolite carrier thereto;
[0171] (11) After heating to 75°C, add 6.05 g of LiCl·H2O and stir to react for 24 hours;
[0172] (12) After filtration, the product was thoroughly washed, dried, and calcined in a muffle furnace at 500 °C for 24 h to obtain a zeolite-supported composite material for lithium ion extraction.
[0173] Using the same instrument as in Example 1, it was determined that the zeolite mass accounted for 92.8%, the silicon-aluminum ratio was approximately 3.18, the grain size was approximately 500 nm, and the aluminum-based lithium ion sieve mass accounted for 5.1%;
[0174] The specific surface area of the zeolite-supported composite material for lithium ion extraction is 52.5 m 2 / g, pore size is about 10-12nm;
[0175] Test example:
[0176] Simulated brine containing various ion concentrations was prepared, including: Li+ (5.250 g / L), Na+ (302.042 g / L), K+ (42.212 g / L), and Mg2+ (0.027 g / L). 2 g of each of the composite materials prepared in Examples 1-3 was placed in 30 ml of the simulated brine for lithium ion adsorption testing. The adsorption was stirred for 2.5 hours. The composite materials were removed, dried, and weighed. The adsorbed materials were then acid-washed and desorbed with 50 ml of an acid wash solution for 2.5 hours. The Li+ content in the brine and acid wash solution after adsorption was determined using ICP.
[0177] Test results are shown in Table 1
[0178] Serial number Li+ adsorption rate % Adsorbent dissolution rate Li+ desorption rate % Example 1 95.2 ≤2.3% 97.3 Example 2 96.1 ≤2.0% 97.1 Example 3 97.9 ≤2.1% 97.3 Example 4 98.5 ≤2.2% 97.9 Example 5 97.3 ≤2.0% 97.2 Example 6 96.9 ≤1.9% 97.5
[0179] By observing and comparing the test results, it is shown that the zeolite-loaded composite material for lithium ion extraction prepared by the present invention has high selectivity for lithium ions and strong adsorption capacity. In addition, the adsorbent is loaded on the carrier, and its dissolution rate is greatly reduced after use. It can be used repeatedly with high adsorption and desorption rates, proving that the composite material of the present invention is an excellent adsorbent for lithium ions in salt lakes.
[0180] Comparative Example:
[0181] Natural zeolite was used as a lithium ion adsorbent carrier to synthesize a composite material, and three sets of parallel experiments were performed.
[0182] Since the natural zeolites used are of different sizes and contain some impurities, they need to be pretreated before modification, including screening and cleaning, to improve the carrier performance.
[0183] Take a certain amount of natural zeolite and place it in a glass beaker filled with deionized water. Stir and wash it thoroughly. Filter out the turbid liquid after precipitation. Repeat this process several times until no turbid liquid appears and no visible floating impurities appear after stirring and standing. Take out the natural zeolite particles, filter them and place them in an oven. Dry them at 105°C for 2 hours, then take them out and put them into a ziplock bag for later use.
[0184] A certain amount of natural zeolite is sieved to obtain zeolites of different particle sizes. Three groups of particle size ranges are selected, namely 0.18-0.38 mm, 0.15-0.18 mm, and 0.12-0.15 mm.
[0185] Composite materials are prepared respectively from the natural zeolites in the three particle size ranges mentioned above.
[0186] The lithium ion adsorption test was carried out in the simulated brine configured as above. The test results are shown in Table 2.
[0187]
[0188] From the results in Tables 1 and 2 above, it can be seen that the use of natural zeolite as an adsorbent carrier, although it is widely available and low in price, requires pretreatment to remove impurities, which is cumbersome and not conducive to industrial production. At the same time, natural zeolite particles vary in size and need to be sieved, and their pore sizes are uneven. The resulting composite material has a small specific surface area, poor stability, a high adsorbent dissolution rate, and low lithium ion adsorption and desorption rates. Therefore, the composite material prepared by using artificially synthesized Y-type zeolite as an aluminum-based adsorbent carrier has its unique advantages.
[0189] The composite material provided by the present invention selects an aluminum-based adsorbent that is simple to prepare and has high stability, and the aluminum-based lithium ion adsorbent is loaded on a synthetic zeolite material, which has good selective adsorption for lithium ions; the adsorbent is tightly connected in the synthetic zeolite carrier, and the ion sieve skeleton has a low dissolution rate. The overall composite material is more sustainable than the direct use of a single aluminum-based adsorbent; the synthetic zeolite is a porous adsorption material, which has a larger specific surface area than natural zeolite as an adsorbent carrier, and does not produce impurities, is pollution-free to the environment, and can simplify subsequent process flows; the present invention uses aerosil with a large specific surface area, high surface activity, and is easy to disperse for reaction. As the silicon-aluminum ratio of the synthetic zeolite material increases, the stability of the composite material is further enhanced, making it suitable for large-scale lithium extraction process applications; the composite material has a moderate preparation cost, a simple process, and is easy to operate, making it suitable for industrial production.
[0190] Those skilled in the art will appreciate that the above-described embodiments are specific examples of the present invention and that, in actual practice, various modifications may be made thereto in form and detail without departing from the spirit and scope of the present invention. Steps or processes not described in detail in this embodiment are commonly known in the industry and are not described in detail here.
Claims
1. A method for preparing a zeolite-supported composite material for lithium ion extraction, characterized in that: The steps include: Step 1) synthesizing medium-pore high-silicon Y-type zeolite; Step 2) Synthesis of amorphous Al(OH)3 powder; Step 3) dissolving the amorphous Al(OH)3 powder of step 2) in ultrapure water and stirring until completely dispersed; then adding the medium-porous high-silicon Y-type zeolite synthesized in step 1), adding LiCl·H2O at 50-75°C for reaction for 20-40 hours, filtering and fully washing, drying, and calcining at 400-500°C for 12-48 hours to obtain a zeolite-supported composite material for lithium ion extraction, wherein the mass ratio of amorphous Al(OH)3 powder to ultrapure water is (0.8-1.1):(98-100), and the mass ratio of amorphous Al(OH)3 powder to LiCl·H2O is (0.9-1.2):(1.02-1.28); The pore size of the medium-pore high-silicon Y-type zeolite is 2-30 nm, and the Si / Al ratio is 3-20; The step 1) synthesizing the mesoporous high-silicon Y-type zeolite adopts an organic amine-free hydrothermal system to synthesize the mesoporous high-silicon Y-type zeolite, comprising the following steps: Sodium aluminate, fumed silica, water and anhydrous ethanol are used as raw materials and prepared in a molar ratio of (8-12):12:160:(5-17.15); Sodium aluminate is added to water according to the formula amount, stirred for 0.5-1h, sodium hydroxide is added to adjust the pH to 7-8, and then anhydrous ethanol is added in the formula amount, and then ultrasonic treatment is performed for 2-10min; finally, a formula amount of fumed silica is added, and after aging in a 22-27°C water bath for 12-36h, the obtained gel mixture is crystallized in a 60-90°C oven for 6-48h; after the crystallization is completed, the product is washed with distilled water until it is neutral, and is placed in a sodium chloride solution with a mass percentage concentration of 28-32% and boiled for 2-4h, and then dried to obtain a medium-pore high-silicon Y-type zeolite; Or the step 1) synthesizing the mesoporous high-silicon Y-type zeolite by using the CTAB / fatty alcohol polyoxyethylene ether ammonium sulfate method to synthesize the mesoporous high-silicon Y-type zeolite comprises the following steps: Sodium aluminate, fumed silica, water, CTAB or fatty alcohol polyoxyethylene ether ammonium sulfate are used as raw materials and prepared in a molar ratio of (8-9):12:160:(11-13); Add sodium aluminate to water according to the formula amount, stir for 0.5-1h, add sodium hydroxide to adjust the pH to 7-8, then add the formula amount of CTAB or fatty alcohol polyoxyethylene ether ammonium sulfate and stir thoroughly, then add the formula amount of fumed silica, age in a 22-27°C water bath for 12-36h, and crystallize the obtained gel mixture in a 60-90°C oven for 6-48h; after the crystallization is completed, wash the product with distilled water until it is neutral, put it into a sodium chloride solution with a mass percentage concentration of 28-32% and boil it for 2-4h, and then dry it to obtain a medium-pore high-silicon Y-type zeolite; Or the step 1) synthesizing mesoporous high-silicon Y-type zeolite, using TPOAC method to synthesize mesoporous high-silicon Y-type zeolite, comprising the following steps: (1) preparing a structure directing agent using sodium aluminate, fumed silica and water as raw materials in a molar ratio of (30-35): (12-16): (322-326); Add sodium aluminate to water according to the formula amount, stir for 25-35 minutes, add sodium hydroxide to adjust the pH to 7-8, then add the formula amount of fumed silica, stir for 2-24 hours and use it as a structure directing agent for later use; (2) Sodium aluminate, fumed silica, water, hydrochloric acid, TPOAC and a structure directing agent are used as raw materials to prepare a medium-pore high-silicon Y-type zeolite in a molar ratio of (4.2-4.8):(8.2-8.6):210:(4-5):0.09:11.7; At room temperature, hydrochloric acid and sodium aluminate are dissolved in water according to the formula amount, stirred for 0.5-1h to obtain a white solution, fumed silica is added according to the formula amount, and after stirring for 2-5h, the structure directing agent prepared in step (1) is added dropwise according to the formula amount, and after stirring for 0.5-1h again, TPOAC is added dropwise in the formula amount, and then crystallized in an oven at 60-90°C for 72-120h; after the crystallization is completed, the product is washed with distilled water until neutral, and placed in a sodium chloride solution with a mass percentage concentration of 28-32 and boiled for 2-4h, and after drying, it is calcined in a muffle furnace at 500-600°C to obtain a medium-pore high-silicon Y-type zeolite.
2. The method for preparing a zeolite-supported composite material for lithium ion extraction according to claim 1, characterized in that: The hydrochloric acid is dilute hydrochloric acid, and the mass percentage concentration is: 6.5-7.0wt%.
3. The method for preparing a zeolite-supported composite material for lithium ion extraction according to claim 1, characterized in that: Step 2) Synthesis of amorphous Al(OH)3: Prepare 500 ml of sodium aluminate solution, add 2-4 ml of polyethylene glycol 1000 solution to the solution, add hydrochloric acid solution dropwise to the solution with stirring until the pH is 5.8-6.2 to reach the reaction end point, continue the reaction for 15-25 minutes, filter and separate the product, wash and dry it to obtain amorphous Al(OH)3 powder.
4. The method for preparing a zeolite-supported composite material for lithium ion extraction according to claim 3, characterized in that: The molar concentration of the sodium aluminate solution is 0.4-0.6 mol / L.
5. The method for preparing a zeolite-supported composite material for lithium ion extraction according to claim 3, characterized in that: The mass percentage concentration of the polyethylene glycol 1000 solution is 8-12%.
6. The method for preparing a zeolite-supported composite material for lithium ion extraction according to claim 3, characterized in that: The molar concentration of the hydrochloric acid solution is 1.8-2.1 mol / L.
Citation Information
Patent Citations
Mesoporous Y-type zeolite molecular sieve and preparation method thereof
CN103214003A
Method for preparing high-performance brine lithium-extraction adsorption agent and adsorption agent prepared by method
CN104014308A
Lithium extraction adsorbent and preparation method thereof
CN113578252A